Effect of tea soil acidification on the diversity and function of fungi community - Jiang Hua Ye (Julius Kühn-Institut, 2021)
Soil fungi play an important role in the process of planting tea tree. However, effects of acidification on the diversity and function of the fungi community in tea rhizosphere soil have been rarely reported. In this study, tea rhizosphere soils with pH of 3.3, 4.7, 5.3 and 6.4 were investigated for diversity and function of fungal communities through T-RFLP technology. The results showed that the abundance and diversity of fungi increased significantly with the decrease of pH value of rhizosphere soil. The results of significance analysis showed that 38 T-RFs fragments were significantly correlated with pH value, among which 32 were negatively correlated with pH value and 6 were positively correlated with pH value. After database comparison, 23 fungi were identified and classified according to their nutritional patterns, which can be divided into four types, including pathotroph, symbiotroph, saprotroph and unknown, accounting for 36.85%, 7.89%, 15.79% and 39.47%, respectively. At pH value of 3.3, the fungus abundance reached the maximum value. In conclusion, acidification leads to changes in the structure and diversity of the fungi community in tea rhizosphere soil, specifically, a significant increase in the number and species of fungi, of which the pathotroph type is the largest. This study provides an important theoretical basis for controlling fungal diseases of tea tree in acidified tea plantations